Yield sustainability in mango (Mangifera indica) as influenced by different levels of foliar Zn sprays - ADAK, TARUN; KUMAR, KAILASH; PANDEY, G; SINGH, VINOD KUMAR (The Indian Journal of Agricultural Sciences, 2022)
Zn nutrient technology impacting mango (Mangifera indica L.) sustainability and nutrient components in pulp, peel and stone of fruit needs to be addressed on sandy loam soils for farmers’ benefit. ICAR networking field trials on micronutrient management in horticultural crops for enhancing yield and quality were conducted at ICAR-CISH, Rehmankhera, Lucknow during 2015–18. The results showed highest sustainable yield index of 0.87 followed by 0.83 with least sustainable yield index of 0.67. The yield increment was 4.3–27.1% in different levels of Zn (0.25%, 0.50%, 0.75%, 1.0%, 1.5% and 2.0% ZnSO4) as compared to control plot trees. Nutrient components suggested significant positive role of Zn application at different fruit setting to developmental stages. Maximum B, Zn, Cu, Mn and Fe was noted to be 28.1 ppm, 8 ppm, 26 ppm, 40 ppm, 119 ppm, respectively, along with P & K content of 0.123%, 2.01%, respectively, in pulp of Dashehari fruits. Similar changes in peel and stone nutrient content were also observed. Data indicated that optimum to sufficient range of micronutrients is indeed required for better yield sustainability in mango.